PERANCANGAN ANIMASI 3D SEBAGAI MEDIA PENGENALAN KERAGAMAN PAKAIAN ADAT DAERAH DI INDONESIA - Noor Afela Salsabila; Anung Rachman; Rendya Adi Kurniawan (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2024)
The diversity of Indonesian culture, such as regional traditional clothing, is a valuable cultural heritage and needs to be preserved. To introduce the diversity of traditional clothing, 3D animation videos can be an effective alternative educational medium. This design aims to create a short 3D animation video that introduces a variety of traditional Indonesian clothing, especially for elementary and junior high school students. This animation design method used is the (MDLC) method and combined with the modeling method (production-pipeline 3D animation) in making the characters. The result of this design is a short 3D animation video which after going through a perception test it is stated that this animation is quite effective and interesting as an educational medium and an introduction to various regional traditional clothes in Indonesia. Keywords: 3D animation; Regional Traditional Clothing; Indonesia